24 An Epidemic of HFPEF?. (3rd June 2016) - Thompson, Alexandra; Crilley, Jenifer; Wilson, Douglas; Hungin, APS; Fuat, Ahmet; Murphy, Jerry
Abstract : Introduction: There is debate about the diagnostic profile of the heart failure population. Diagnostic criteria for heart failure with reduced ejection fraction (HFREF) are variable and many believe that heart failure with preserved ejection fraction (HFPEF) is over-diagnosed. There is also differing opinion about whether these conditions are distinct entities. The aim of this study was to differentiate a heart failure population with contemporary diagnostic parameters. Methods: A diagnostic pathway using current best evidence for the diagnosis of HFREF and HFPEF was created. This was applied prospectively to all 319 new patients attending our heart failure clinic between May 2013 and July 2014. Results: 245 of the 319 new patients were deemed to have heart failure clinically. 73% met our diagnostic criteria for HFREF (LVEF <55%), and only 14% met the diagnostic criteria for HFPEF. Changing the LVEF threshold to <40% produced a ratio of HFREF to HFPEF of 1.3:1 which is more in keeping with current perceptions about an epidemic of HFPEF, but reflects the fact that many of those diagnosed with HFPEF have a definite reduction in LVEF that could account for their presentation. A requirement for elevated LV diastolic pressures or elevated biomarkers +/-diastolic dysfunction to justify a diagnosis of HFPEF resulted in a number of individuals being reclassified as having no major structural heart disease. Subset analysis of the 25 patients that maintained a diagnosis of HFPEF following a more detailed echo and MRI showed that 76% had convincing markers of LV systolic dysfunction despite a normal LVEF. Conclusions: Variable diagnostic boundaries mean some definitions of HFPEF incorporate more people with subtly reduced LVEF than others. A set of positive criteria for the diagnosis of HFPEF remains challenging and resting echocardiographic measurements have significant limitations. Currently, no universal diagnostic pathway has been agreed but our framework and analysis help better understand the HFPEF phenomenon.